Perioperative management with biologics on severe aortic valve regurgitation caused by Behçet syndrome: the experience from a single center - Luxi Sun; Jinjing Liu; Xiufeng Jin; Zhimian Wang; Lu Li; Wei Bai; Yunjiao Yang; Chanyuan Wu; Wei Chen; Shangdong Xu; Jun Zheng; Wenjie Zheng (SAGE Publishing, 2021)
Background: To investigate the efficacy and safety of biologics in the perioperative management of severe aortic valve regurgitation (AR) caused by Behçet syndrome (BS). Methods: We retrospectively analyzed 20 patients with severe AR caused by BS who were all treated with biologics during the perioperative period of cardiac surgeries in our center between February 2016 and October 2020. Results: A total of 20 patients with severe AR were enrolled, including 19 males and 1 female, with a mean age of 39.1 ± 8.8 years and a median course of 8 [interquartile range (IQR) 5.25-10.00] years. Before biologic administration, 92.9% of the patients who underwent aortic valve replacement had failed conventional therapy and developed postoperative paravalvular leakage (PVL) at a median interval of 4 months. Biologics were administered with background glucocorticoids (GCs) and immunosuppressants during the perioperative period for 22 aortic valve surgeries, including preoperatively with a median interval of 3.5 (IQR 2.75-4.25) months in 13 cases and within 3 months postoperatively in 9 cases. After a median follow up of 21 (IQR 15-32) months, 2 out of 13 cases (15.4%) preoperatively, and 1 out of 9 cases (11.1%) postoperatively treated with biologics developed PVL, and the rest were event free. The Behçet's Disease Current Activity Form score improved significantly (7 versus 0, median, p  < 0.0001). Decrease of erythrocyte sedimentation rate [25.0 (IQR 11.00-36.25) mm/h versus 6.5 (IQR 4.0-8.8) mm/h, p  < 0.001], and C-reactive protein [20.77 (IQR 7.19-29.58) mg/l versus 1.53 (IQR 0.94-2.92) mg/l, p  = 0.001] were achieved rapidly and effectively. The GC dosage tapered from 40 (IQR 30-60) mg/d to 10 (IQR 5-11.25) mg/d, p  < 0.0001. Immunosuppressants were tapered in number and dosage in 6 (30%) and 20 patients (100%), respectively. No serious adverse event was observed. Conclusion: Our study suggests that biologics were effective and well tolerated for the perioperative management of severe and refractory AR caused by BS, which significantly reduced the occurrence of postoperative PVL and had favorable GC- and immunosuppressant-sparing effect.